Kemampuan literasi pada siswa kelas II di SD Negeri 89 Palembang - Nabella Gusta Latifa; Nyiayu Fahriza Fuadiah; Eka Fitri Puspa Sari (COLLASE (Creative of Learning Students Elementary Education), 2026)
This study aims to determine the Literacy Skills of Second Grade Students at State 89 Palembang Elementary School. In this study the method used was descriptive quantitative, data collection was carried out using an instrument in the form of an essay question test. 9 questions that were declared valid and reliable, 10 essay questions that were tested obtained 10 easy questions, in this study were 9 essay questions (1,2,3,4,6,7,8,9,10) the reason for retaining 9 questions was seen from the analysis of the trial results that had met the eligibility criteria and each question had met the indicators. Based on the results of data analysis and research conducted in class II SD Negeri 89 Palembang, it can be concluded that students' mathematical literacy skills in multiplication material are in the medium category. This is indicated by the average student score of 58.66 and the achievement of mathematical literacy understanding indicators with a percentage of 56%. Overall, this indicates that students' basic mathematical literacy skills in solving multiplication problems are still moderate.